The impact of board attributes and ownership concentration on firm market value: empirical evidence from an emerging market - Alhassan Bunyaminu; Ibrahim Nandom Yakubu; Seydou Oumarou (Cogent Business & Management)
This study investigates the relationship between corporate governance mechanisms and firm market value using data from listed firms on the Ghana Stock Exchange spanning 2008 to 2018. Employing the generalized method of moments (GMM) regression technique, the study examines the impact of various governance variables on market value added (MVA). The findings reveal significant linkages between specific governance variables and MVA. Notably, outside directors, gender diversity, frequency of board meetings, and audit committee size are found to significantly reduce firm value. Conversely, CEO duality and ownership concentration positively impact firm market value. The study further observes that while leverage has a significant positive impact on MVA, the effect of firm age is negative. The study recommends that stakeholders, including regulatory bodies and corporate boards, prioritize initiatives to enhance board diversity by fostering a balanced mix of internal and external directors, as well as promoting gender diversity. Additionally, optimizing the frequency of board meetings and ensuring appropriate audit committee sizes are emphasized to strengthen governance structures and improve firm value.